The Implementation of Project-based Learning (RETAIN, 2020)
The aim of this article is to know the implementation of Project-based learning. One of requirements that is needed to be achieved by English learner is to be able to speak in a target language. Nevertheless, even the students have already learnt English since in the elementary school, it cannot grant them to speak fluently. It is because, the teaching learning process emphasizes reading skill rather than speaking. As a result, students are not accustomed to speak in a target language. They never practice and correct their mistake. Since there is no mistake corrected, they will never realize which parts of their utterance that must be fixed. Therefore, this issue needs to be concerned. The students need to be trained to speak in a target language thus they can communicate both written and oral using a proper English. One of possible methods that can be used by the teacher is Project-based Learning. Project-Based learning refers to a model that organizes learning around project. The students are required to create a project which will be demonstrated at the end of the lesson. This research used qualitative design. This study was conducted in classroom. The subject of this study was a teacher of senior high school in a big city. The data were collected through observation by using field note. After the data were collected, they were analyzed through three steps which are transcribing, categorizing, and interpreting. The result of this study showed that there are six steps of implementation of Project-based learning namely giving essential question, designing a plan for a project, creating a schedule, monitoring the students and progress of the project, assessing the outcome, and culminating in the evaluating experience.